High-performance composite anodes based on SBA-15 mesoporous silica modified with silicon, silicon oxide, titanium oxide, and germanium oxide for lithium-ion batteries - Andrei, Radu Dorin; Ungureanu, Giorgian Cosmin; Mandoc, Luisa Roxana; Niculescu, Violeta-Carolina; Rodriguez, Jeremy; Buga, Mihaela Ramona; Tiliakos, Athanasios (Applied surface science advances, 2025)
In this study, SBA-15 mesoporous silica was modified with silicon, silica, titania, and germania particles to prepare composite silica-based anodes for lithium-ion batteries. The materials and the ensuing anodes were extensively characterized at every stage of their synthesis and preparation (BET/BJH, XRD, SAXS, FTIR, SEM, EDX) and the electrochemical performances of the assembled composite anodes were audited by voltammetric and galvanostatic methods to determine their discharge capacities and coulombic efficiencies. The composite anodes, especially Ti/SBA-15 and Ge/SBA-15, displayed stable coulombic efficiencies and gradually increasing capacities with steady trends, with the Ti/SBA-15 anode reaching 240 mAh g–1 and the Ge/SBA-15 one rising higher at 550 mAh g–1 after 500 cycles, thus outperforming the Si/SBA-15 anode which, in contrast, reached the high mark of 550 mAh g–1 within the first 50 cycles but continued with gradually diminishing performance and unstable efficiency. With indications of the underlying driving phenomenon pertaining to electrochemical grinding effects, our work encourages further investigations on the highly probable outcome of much increased lifetimes and higher performances for these types of composite anodes for lithium-ion batteries.